Bacterial meningitis in a known case of steroid-resistant nephrotic syndrome - Bunde, Saili Vishwanath; Sharif, Mumtaz; Saxena, Amit (Indian Journal of Child Health, 2021)
Nephrotic syndrome (NS) is a kidney disorder in which, excess protein is being excreted through urine. While most cases of idiopathic nephrotic syndrome respond to steroid therapy and experience a limited number of relapses prior to complete remission, some cases suffer from frequent relapses and become steroid-dependent or are primarily steroid-resistant. Treatment options are limited to immunosuppressive drugs with significant side effect profiles. Infections in nephrotic syndrome are common and can be severe. Meningitis is one of the complications associated with nephrotic syndrome. Here, we report a child with steroid-resistant nephrotic syndrome (SRNS) with meningitis. Early detection and appropriate treatment of these complications can be lifesaving.